Emerging market real estate investment : investing in China, India, and Brazil - Lynn, David J. (Hoboken, N.J. : Wiley, 2010)
'This book outlines private equity real estate investment strategies for emerging markets internationally, and focuses on three of the most dynamic and important emerging market countries: China, India and Brazil.' --
Includes bibliographical references (p.217-218) and index.
Keywords: Real estate investment -- China; Real estate investment -- India; Real estate investment -- Brazil